Sexually transmitted diseases and HIV-1 infection among homosexual men in England and Wales. Issue 6875 (13th February 1993) - Evans, B G; Catchpole, M A; Heptonstall, J; Mortimer, J Y; McCarrigle, C A; Nicoll, A G; Waight, P; Gill, O N; Swan, A V
Abstract : OBJECTIVE–To examine surveillance data for evidence of changing sexual behaviour and continuing transmission of HIV-1 among men who have sex with men. DESIGN–Analytic study of surveillance data on sexually transmitted diseases. SETTING–England and Wales. MAIN OUTCOME MEASURES–Number of cases of rectal gonorrhoea and newly diagnosed HIV infection in homosexual men. RESULTS–New cases of gonorrhoea among men attending genitourinary medicine clinics increased by 7.7% in 1989 and by 4.2% in 1990. Reports of rectal isolates of Neisseria gonorrhoeae also rose and the male to female ratio for patients with rectal gonorrhoea changed from 0.3:1 during 1988-9 to 2.6:1 in 1990-1. Although the overall number of cases of acute hepatitis B fell during 1988-91, 81 and 82 homosexual men were infected in 1990 and 1991 respectively compared with 50 and 42 in 1988 and 1989. 1526 men had HIV-1 infection diagnosed in 1991, the largest number since 1987. Twenty eight of the 97 (29%) men who seroconverted between January 1989 and December 1991 were aged less than 25. The proportion of men aged 15-19 who were found to be infected with HIV-1 at their first test increased from an average of 2.4% up to 1990 to 4.7% in the first nine months of 1991. The prevalence of HIV infection in men under 25 attending genitourinary medicine clinics in London was 17% compared with 7.8% outside London. CONCLUSION–Unsafe sexual behaviour and HIV transmissions have increased among homosexual men after a period of decline. Recent HIV transmissions may disproportionately affect younger men.